Sound waves in science education: as a learning facilitator (Research, Society and Development, 2020)
The Science Education can acquire new courage when using different forms of education, to be used in support of building tools and concepts such as musical instruments. The objective of this work was to develop science classes, contextualizing music to facilitate the understanding of wave phenomena, their application, importance and to assess students' prior knowledge, their way of observing content, using the meaningful concepts of learning. Therefore, the qualitative approach was adopted according to the characteristics indicated by Bogdan and Biklen (1994) and the design of a Case Study according to Gil (2008). It was noticed that a different approach, using musical tools for fixing the content in order to achieve a better understanding and acceptance of the theme. The results were positive with respect to the setting contents of an acceptance of the methodology used, and the secondary objective which is to provide a first contact with musical instruments, and the construction of whistles, for construction of undulatory concepts.